The Relationship Between Stress Levels, Body Image, and High Sodium Eating Behavior with Nutritional Status Among Female Adolescents At SMA Negeri 2 Palu - Rahma Rizkina; Nikmah Utami Dewi (Journal of Community Nutrition Intervention, 2025)
Adolescent girls are a group vulnerable to nutritional problems due to physical, psychological, and social changes that influence eating patterns. Nutritional status plays an important role in supporting optimal health. This study aims to evaluate the relationship between stress levels, body image, high sodium food consumption behavior, and nutritional status in adolescent girls in Palu City. This study employed a cross-sectional design with a sample of 110 adolescent girls aged 15–18 years selected using simple random sampling at a State Senior High School in Palu City. Data collection was performed using the Perceived Stress Scale (PSS) questionnaire to measure stress levels, the Body Shape Questionnaire (BSQ) to assess body image, and the Food Frequency Questionnaire (FFQ) to evaluate high-sodium eating behavior. Nutritional status was measured based on BMI-for-age. Bivariate analysis was conducted using the Spearman rank test, while multivariate analysis utilized ordinal logistic regression. The results of the univariate analysis revealed that the majority of adolescent girls had a good nutritional status (78.2%), moderate stress levels (83.6%), and a negative body image (70.0%). The frequency of high sodium food consumption was mostly found in the rare category (39.1%). Bivariate analysis revealed no significant relationship between stress levels (p-value = 0.379) or body image (p-value = 0.838) and nutritional status. However, high sodium eating behavior had a significant relationship with nutritional status (p-value 0.002). Multivariate analysis also demonstrated that high sodium eating behavior remained a significant factor associated with the nutritional status of adolescent girls.